EKSISTENSI PENGADILAN PAJAK DALAM PENYELESAIAN SENGKETA PAJAK - Hasan Basri (Nusantara Hasana Berdikari, 2021)
Tax is a mandatory contribution to the state that is owed by an individual or legal entity that is coercive based on the law. Taxpayers must pay taxes because taxes are one of the state revenues used for national development. In fact, there are still often differences between taxes and mandatory tax authorities in the provisions of laws and regulations, this often leads to tax disputes. The formulation of the problem in this study are: 1) What is the position of the Tax Court in Indonesia? 2) What are the obstacles in resolving tax disputes? This research is expected to increase legal knowledge, especially regarding the Tax Court and the creation of a tax court that provides legal certainty and justice for the community. This study uses a normative research method with a statutory and conceptual approach. The results of the study show that: 1) the position of the Tax Court is not independent, meaning that the Tax Court is under the guidance of 2 (two) institutions, the first is technical guidance by the Supreme Court (Judicative), the second is organizational, administrative, and financial development by the Ministry of Finance (Executive). ). This condition resulted in the independence of the Tax Court, especially the judges in giving decisions. 2) The obstacle in the process of resolving tax disputes is the location of the Tax Office which is in the State Capital, this is not in accordance with the fast, simple and low-cost trial.